2016
DOI: 10.1177/1077558716655451
|View full text |Cite
|
Sign up to set email alerts
|

Improving Heart Failure Outcomes in Ambulatory and Community Care: A Scoping Study

Abstract: Despite a large body of literature testing interventions to improve heart failure care, care is often suboptimal. This scoping study assesses organizational interventions to improve heart failure outcomes in ambulatory settings. Fifty-two studies and systematic reviews assessing multicomponent, self-management support, and eHealth interventions were included. Studies dating from the 1990s demonstrated that multicomponent interventions could reduce hospitalizations, readmissions, mortality, and costs and improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 96 publications
(118 reference statements)
0
20
0
Order By: Relevance
“…35 Heart failure disease management programs were evaluated in the 1990s and showed significant reductions in hospitalizations, readmission rates, quality of life, and cost. 36 Similar programs in diabetes, 37 chronic obstructive pulmonary disease, and cirrhosis care have shown similar improved outcomes. 38,39 Chronic disease management programs also address hospital readmissions and mortality, although these are not important issues for FGIDs.…”
Section: Discussionmentioning
confidence: 95%
“…35 Heart failure disease management programs were evaluated in the 1990s and showed significant reductions in hospitalizations, readmission rates, quality of life, and cost. 36 Similar programs in diabetes, 37 chronic obstructive pulmonary disease, and cirrhosis care have shown similar improved outcomes. 38,39 Chronic disease management programs also address hospital readmissions and mortality, although these are not important issues for FGIDs.…”
Section: Discussionmentioning
confidence: 95%
“…57 59 60 One review reported a moderate-to-large positive effect of THA on quality of life. 59 One review found mixed evidence of interventions on quality of life among heart failure 57 patients and one review found no significant difference in quality-of-life outcomes among patients with COPD 60 when interventions were delivered in outpatient or community settings.…”
Section: Hospital In the Homementioning
confidence: 99%
“… 3 5 Although most nursing interventions or disease management programs are provided based on guidelines, limited studies regarding intervention components and implementation methods have been available. 6 Therefore, Pinchera et al proposed that optimal intervention strategies should be individualized to suit the patients’ chronic condition and included in multicomponent and eHealth interventions. 6 , 7 However, Jonkman et al 8 stated that self-management interventions show great diversity in terms of mode, content, intensity, and duration.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Therefore, Pinchera et al proposed that optimal intervention strategies should be individualized to suit the patients’ chronic condition and included in multicomponent and eHealth interventions. 6 , 7 However, Jonkman et al 8 stated that self-management interventions show great diversity in terms of mode, content, intensity, and duration. On the other hand, patients with HF receive ambiguous advice, display inconsistent behavior and symptoms, are impacted by socioeconomic factors, have poor adherence, become disappointed due to failure despite practice, have physical and psychosocial restrictions due to HF, and poor psychological response to restrictions from medical professionals, all of which leads to worsening of symptoms.…”
Section: Introductionmentioning
confidence: 99%